2013
DOI: 10.1111/nhs.12071
|View full text |Cite
|
Sign up to set email alerts
|

Surviving depressive ill‐health: A qualitative systematic review of older persons' narratives

Abstract: Reaching out of loneliness towards aloneness and connectivity. Further research should be focused on how community projects can improve health services such as enhancing the safety of health care and disseminating health information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 61 publications
(253 reference statements)
2
26
0
Order By: Relevance
“…It might inhibit the older people from seeking treatments. This is in line with previous studies that reported that patients with depression did not seek treatment because they lacked knowledge (Epstein et al, 2010), and because they hide due to a feeling of shame (Holm & Severinsson, 2014). This study has shown that the older people feeling judged by surrounded people.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…It might inhibit the older people from seeking treatments. This is in line with previous studies that reported that patients with depression did not seek treatment because they lacked knowledge (Epstein et al, 2010), and because they hide due to a feeling of shame (Holm & Severinsson, 2014). This study has shown that the older people feeling judged by surrounded people.…”
Section: Discussionsupporting
confidence: 82%
“…Another field of the research have focused on the perspective of the patients with depression. For instance, a literature synthesis of older persons' narratives showed that, when suffering from depression they engaged three central strategies to survive; the need for courage, strength and self-reliance; the meaning of responsibility; and wearing a mask of normalcy to hide shame (Holm & Severinsson, 2014). While, the perspective from patients' family showed that to them the relative's major depression was trying and that it brought them into severe stressful life situations (Ahlstrom, Skarsater, & Danielson, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review of older persons' narratives when suffering from depressive ill-health revealed three themes; "the need for courage, strength, and self-reliance", "the meaning of responsibility", and "wearing a mask of normalcy to hide the shame" [15]. Moreover, exploring older persons' lived experiences of depression and self-management revealed the theme "relationships and togetherness" [32].…”
Section: Discussionmentioning
confidence: 99%
“…Kneafsey, Brown [19] used the method to analyze healthcare professionals' compassion perceptions to reveal four overarching components of the concept. Holm and Severinsson [20] used thematic analysis to identify key patterns found in geriatric patients' narratives regarding their experiences of surviving with depression. Hickey, Sumsion [21] employed thematic analysis in their mixed-method, longitudinal study of factors that influence nurses' career choices and aspirations.…”
Section: Overviewmentioning
confidence: 99%